Manajemen Parkir dan Dampaknya terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Aceh Tamiang - Junita, Afrah; Muhammad Ridla; Agus Putra AS; Junita Safitri; Muhammad Salman (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
The aim of the research is to identify, inventory and assess parking problems and their impact on increasing PAD in Aceh Tamiang Regency. The research method used is a qualitative method. Data was collected through observations and in-depth interviews, informants were determined based on the suitability of research indicators. The location of research is the Aceh Tamiang. The results explain that the Aceh Tamiang Regional Government is currently still hampered by several things, such as the lack of strong human resources for collecting and managing taxes and levies in each regional apparatus; there is still resistance, both active and passive, from parking attendants; the database is incomplete and requires further improvement and there is no regular evaluation of the development of potential parking levies that have been managed by the government or levies that have the potential to become a source of new regional revenue.